Analisis Kejelasan Anggaran, Efektivitas Kinerja Anggaran & Pengawasan Keuangan Dalam Pelaksanaan Apbd Tahun 2022 Kota Bltar - Theresia Uli Sianturi; Hwihanus Hwihanus (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2024)
This research aims to analyze budget clarity, the effectiveness of the budget team's performance, and regional financial supervision in overcoming implementation problems related to the implementation of the Regional Revenue and Expenditure Budget (APBD) for Fiscal Year 2022 in Blitar City. With a comprehensive analytical approach, this research identifies critical factors that influence the success of APBD implementation, evaluates the level of budget clarity, measures the effectiveness of the budget team's performance, and assesses the role of regional financial supervision. It is hoped that the research results will provide in-depth insight for stakeholders in improving regional financial management and overcoming practical obstacles that may arise in the implementation of the 2022 APBD in Blitar City.